Boldness to predator is not significantly correlated with mating behaviour in a simultaneously hermaphroditic snail. Issue 5 (3rd September 2019) - Hamada, Takatoshi; Kuriwada, Takashi
Abstract : If one sex role is preferred over the other, the hermaphroditic mating system might not be maintained. Some simultaneous hermaphroditic species show unilateral mating. Behavioural syndromes that link two behaviours often maintain individual variations in the behaviours. We predict that a behavioural syndrome (boldness) also maintains variation in the sex role decision of the hermaphroditic freshwater snail Physa acuta . Boldness is assumed to reflect an individual's personality to predation risk, and is measured as the latency to emerge from shells after an artificial stimulus. We examined whether the bolder snails exhibit more active mating behaviour such as male role, shorter latency to copulation and longer copulation duration. Significant repeatability indicated that boldness was a consistent trait within an individual. Furthermore, boldness was positively correlated with shell length and negatively with age, respectively. We found no significant relationships between boldness and mating behaviour (sex role, latency to copulate, and copulation duration). Therefore, the behavioural syndrome in the present context is not likely to maintain a sex role preference.